Ultraviolet studies upon phytoplankton from freshwater and marine ecosystems of Argentina - Helbling, Eduardo Walter (2014)
Argentina, with its large latitudinal extent, has an important number of water bodies with different light scenarios therefore, variable responses to solar radiation are found. In this article we review the impact of UVR on phytoplankton from different aquatic ecosystems of Argentina, mostly focusing on targets such as the photosystem and the DNA molecule. Also, we present examples of different acclimation strategies that include, among others, the synthesis of UV-absorbing compounds and shifts in the community composition and structure as a result of UVR exposure. While we have obtained an important database about the effects and impacts of UVR on phytoplankton, especially from the Patagonia area, there are many points still to unveil, mainly those related to the interactive effects of climate change variables such as the increase in temperature and UVR levels, and how this would affect phytoplankton exposure and behaviour in different water bodies.